A perspectiva de Nietzsche sobre verdade, mentira e linguagem - Peres, Ingrid Falcão (2023)
This study approaches the point of view of the German philosopher Friedrich Wilhelm Nietzsche with regards to the concept of truth with emphasis on his 1873 youth essay, entitled About Truth and Lies in the extra-moral sense. An analysis of the author’s argumentative quest will be performed highlighting his understanding of truth and lie, as well as his notion of impulse to truth and truth as a concealment of the intellect. In this sense, it is proposed to understand Nietzsche’s fundamental assumptions for the understanding of his criticism of language, with the aim of demonstrating that truth comes from the human need to live in community. In this context, the author refers to Plato’s philosophy as a denial of life, since this is the reference that permeates the philosophical thought hitherto held under the aegis of true knowledge. Nietzsche redirects these issues to the field of human actions and coexistence between individuals. As a result, it is necessary to consider the way in which he confronts his point of view with the traditional philosophical thought, strictly conceptual, which according to him, is contaminated by Platonic philosophy. In a general way, it defines the supersensible reality as true and unchangeable, and the sensible as the apparent world. Finally, an attempt will be made to understand the relationship between language and truth, based on the meaning that Nietzsche gives to metaphors and, consequently, what are the implications of this movement of formulating and instituting truths in the social atmosphere. Therefore, it is possible to verify that the author opens, so to speak, a new perspective concerning the truth in the philosophy scenario.